PEMBENTUKAN DAN MAKNA GAIRAIGO DALAM BUKU ICHINICHI SEN EN DE ASOBERU MINAMI NO SHIMA KARYA HAYASHI KAZUYO - Putri Kwarini, Ida Ayu (Humanis; Volume 16. No. 2. Agustus 2016)
This research entitled formation and gairaigo meaning in “ichinichi sen en de soberu minami no shima” by hayashi kazuyo. This research aims to examine the formation process that occurs in gairaigo, and to know the meaning gairaigo after being absorbed into Japanese. The theories used for analyzing are morphology theory by Tsujmura and meaning theory by Abdul Chaer. The result of this research is there gairaigo whose meaning can’t be substituted such as hoteru with ryokan. In addition, there are also 42 gairaigo experiencing affixation, 81 gairaigo experiencing compositon, eight gairaigo experiencing clipping and 105 gairaigo experiencing loans.
Keywords: Gairaigo, formation, meaning